Penyusunan Dan Pengembangan Bahan Ajar Perpajakan Untuk SMA Islam Nabilah - Robby Krisyadi; Salma Alfiqi (ConCEPt - Conference on Community Engagement Project, 2021)
The COVID-19 outbreak that hit Indonesia has caused the Indonesian government to issue new policies to carry out online learning and teaching activities. This new policy poses many difficulties, especially for students with the main constraints of learning media that are less interesting and difficult to understand. The preparation and development of teaching materials is aimed at SMA Islam Nabilah with the main goal of simplifying the teaching and learning process. The learning media developed consists of modules, slideshows, and animation videos for grade XI. The material presented refers to the basic competencies from the annual learning syllabus provided by SMA Islam Nabilah. The subject presented includes basic concepts of taxation such as understanding, functions, benefits, to tax rates and their calculations. With modules, slideshows, and video animation learning that has been developed will provide benefits as a reference in the learning process and can be used continuously by the teachers.